1990
DOI: 10.1007/bf01959485
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset myasthenia gravis: Clinical characteristics and response to therapy

Abstract: We studied 59 children with myasthenia gravis (MG). Disease onset was pre-pubertal in 26 patients and post-pubertal in 33. The male to female ratio was 0.62 in the early- and 0.17 in the late-onset groups. The frequency of ocular MG was higher in patients with prepubertal onset. Patients with generalized MG generally showed a good response to thymectomy and corticosteroid therapy proved effective with no major side-effects. In our experience early-onset MG has the same course as in adult life. We recommend thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 15 publications
2
48
1
Order By: Relevance
“…The incidence of juvenile patients who present with purely ocular symptoms (Osserman grade Ia) has been reported to range widely from 27% to 93% in retrospective analyses (Table 1). 4,5,13,17,22,28,29,36,41,43 The variability in presentation appears to be somewhat dependent upon ethnicity. Several studies of Asian children have reported a substantially higher incidence of ocular presentation.…”
Section: Clinical Presentation Natural History and Demographicsmentioning
confidence: 95%
See 2 more Smart Citations
“…The incidence of juvenile patients who present with purely ocular symptoms (Osserman grade Ia) has been reported to range widely from 27% to 93% in retrospective analyses (Table 1). 4,5,13,17,22,28,29,36,41,43 The variability in presentation appears to be somewhat dependent upon ethnicity. Several studies of Asian children have reported a substantially higher incidence of ocular presentation.…”
Section: Clinical Presentation Natural History and Demographicsmentioning
confidence: 95%
“…An analysis of 13 studies that cited the gender distribution of JMG patients revealed a female predominance of between 50% and 86%. [3][4][5]13,22,28,29,36,37,41,43,44 However, prepubertal-age patients (Ͼ12 years of age) ranged from 53% to 73% female, whereas postpubertal-age patients ranged from 77% to 85% female. 3,5,13,28,37 One recent study indicated that patients diagnosed before 10 years of age were equally distributed between male and female, but after age 10 females were five times as likely (P Ͻ 0.01) to be diagnosed in a ratio similar to that for adults.…”
Section: Clinical Presentation Natural History and Demographicsmentioning
confidence: 97%
See 1 more Smart Citation
“…We used neostigmine that showed a positivity similar to the traditional Tensilon test 2,15,16 . We found the longer action of neostigmine somewhat advantageous since we had more time to observe the positive signs, especially in the very young.…”
Section: Discussionmentioning
confidence: 99%
“…2 Indian study of 77 children with MG has revealed an equal sex ratio. 3 MG is caused by serum antibodies(produced mainly by B cells) binding to the nicotine AChR on the post synaptic surface of the NMJ leading to its loss.…”
mentioning
confidence: 95%